2020
DOI: 10.2147/ott.s249494
|View full text |Cite
|
Sign up to set email alerts
|

<p>Circ_0005576 Promotes Malignant Progression Through miR-874/CDK8 Axis in Colorectal Cancer</p>

Abstract: Purpose: To investigate the function of circ_0005576 in colorectal cancer (CRC) progression. Patients and Methods: Circ_0005576 expression in CRC patients was detected by quantitative real-time polymerase chain reaction (qRT-PCR) and in situ hybridization (ISH). CRC cells were transfected using Lipofectamine 2000 reagent. CRC cell proliferation was researched by Cell Counting Kit-8 (CCK-8) assay and 5-ethynyl-2-deoxy-uridine (EdU) incorporation experiment. Cell cycle and apoptosis were determined by flow cytom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 19 publications
0
11
0
Order By: Relevance
“…5 Two previous studies pointed out that hsa_circ_0005576 is an oncogene that can mediate the progression of colorectal cancer and cervical cancer. 12,13 At this time, there have been no other reports on F I G U R E 5 A, Heat map of the transcriptome microarray of differentially expressed genes in H1975OR cells transfected with or without sh-circ_0005576. B, Signaling pathway enrichment analysis by transcriptome microarray for differentially expressed genes of H1975OR cells transfected with or without sh-circ_0005576.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…5 Two previous studies pointed out that hsa_circ_0005576 is an oncogene that can mediate the progression of colorectal cancer and cervical cancer. 12,13 At this time, there have been no other reports on F I G U R E 5 A, Heat map of the transcriptome microarray of differentially expressed genes in H1975OR cells transfected with or without sh-circ_0005576. B, Signaling pathway enrichment analysis by transcriptome microarray for differentially expressed genes of H1975OR cells transfected with or without sh-circ_0005576.…”
Section: Discussionmentioning
confidence: 99%
“…10,11 Recently, hsa_circ_0005576 has been demonstrated to promote malignant progression in colorectal cancer through the miR-874/CDK8 axis. 12 Furthermore, upregulated hsa_circ_0005576 was associated with cervical cancer progression through the miR-153/ KIF20A axis. 13 Nevertheless, the expression patterns and functions of hsa_circ_0005576 involved in EGFR-TKI resistance of LUAD are still almost unknown.…”
mentioning
confidence: 99%
“…As shown in Table 1 , miR-874 is downregulated in at least 22 human malignancies, such as colorectal cancer (CRC) ( Huang et al, 2020a ; Yu et al, 2020 ; Que et al, 2017 ; Zhao and Dong, 2016 ; Han et al, 2016 ; Wang et al, 2021 ; Zhang et al, 2021c ), gastric cancer (GC) ( Huang et al, 2018 ; Sun et al, 2020 ; Yuan et al, 2020 ; Liu et al, 2017 ; Zhang et al, 2015 ; Jiang et al, 2014 ), hepatocellular carcinoma (HCC) ( Zhang et al, 2018b ; Jiang et al, 2017 ; Leong et al, 2017 ; Song et al, 2016 ), esophageal squamous cell carcinoma (ESCC) ( Yuan et al, 2018 ), pancreatic ductal adenocarcinoma (PDAC) ( Diao et al, 2018 ), non-small cell lung cancer (NSCLC) ( Bu et al, 2020 ; Yang et al, 2017 ; Ahmad et al, 2015 ; Kesanakurti et al, 2013 ; Wang et al, 2020b ), osteosarcoma (OS) ( Tang et al, 2018 ; Liu et al, 2020 ; Dong et al, 2016 ; Ghosh et al, 2017 ), epithelial ovarian cancer (EOC) ( Xia et al, 2018 ) cervical cancer (CC) ( Liao et al, 2018 ; Liu et al, 2021a ), retinoblastoma (RB) ( Zhang et al, 2018a ; Wang et al, 2020a ), prostate cancer (PCa) ( Pashaei et al, 2017 ) maxillary sinus squamous cell carcinoma (MSCC) ( Nohata et al, 2011 ), breast cancer (BC) ( Li et al, 2020 ; Zhang et al, 2017 ; Wang et al, 2014 ), triple-negative breast cancer (TNBC) ( Wu et al, 2020 ), rhabdomyosarcoma (RMS) ( Shang et al, 2019 ), papillary thyroid carcinoma (PTC) ( Ding et al, 2021 ), endometrial cancer ( Witek et al, 2021 ), cholangiocarcinoma ( Pan et al, 2021 ), glioma ( Li et al, 2021a ), myeloma (MM) ( Tian et al, 2021 ), head and neck squamous cell carcinoma (HNSCC) ( Nohata et al, 2013 ) and acute myeloid leukemia (AML) ( Zhang et al, 2021a ).…”
Section: The Aberrant Expression Of Mir-874 In Human Diseasesmentioning
confidence: 99%
“…In CRC, the MCF2LAS1/miR-874-3p/FOXM1 axis ( Liao et al, 2018 ) and MCF2LAS1/miR-874-3p/CCNE1 axis ( Huang et al, 2020a ) can promote cancer cell apoptosis, inhibit cancer cell proliferation, invasion, migration and EMT process. Also, the circ_0005576/miR-874/CDK8 axis can promote the malignant progression of CRC ( Yu et al, 2020 ). In CRC cells, circ_0007142 can regulate the level of GDPD5 by sponging miR-874-3p (12).…”
Section: The Cerna Network Centered On Mir-874mentioning
confidence: 99%
“…Circular RNA (circRNA) is a noncoding RNA with high stability [ 4 ], and is generated from the exonic regions of coding gene via back-splicing [ 5 ]. Multiple researches have reported that circRNAs participate in regulating cancer development [ 6 , 7 ]. In particular, circ-ring finger protein 121 (circ-RNF121), only named as circ_100876, regulates the development of digestive system-related cancers.…”
Section: Introductionmentioning
confidence: 99%